PENERAPAN METODE INKUIRI BERBASIS VISUALISASI MUSEUM SANGIRAN UNTUK MENINGKATKAN PRESTASI BELAJAR DAN MENUMBUHKEMBANGKAN KESADARAN SEJARAH SISWA KELAS VII SMP NEGERI 2 SURAKARTA - Fitriah, Chairany; Joebagio, Hermanu; Suryani, Nunuk (HISTORIKA, 2016)
This research aims to: 1 increase the learning achievements); and 2) awareness of history in grade VII JUNIOR HIGH Country 2 Surakarta through the application of methods of Inkuiri-based visualization of Sangiran Museum. This type of research this is a class action Research (PTK). The research was carried out in 3 cycles of action. This research was carried out in junior high Country 2 Surakarta in the first year of lessons 2013/2014. The research was carried out from June to October 2013. The subject of research is the grade VII C of the semester I year 2013/2014 lesson with a population of as many as 32 students. The technique of data collection is done using an engineering test, observation, and documents. Technique of data analysis is done using qualitative data analysis technique that consists of three stages, namely the reduction of data, exposure data, and a false assertion.Based on the results of the analysis, it was concluded: 1) the application of the method of inkuiri-based visualization of Sangiran Museum can enhance the learning achievements of students in the learning of SOCIAL SCIENCE history. This is shown by the increasing value of the results of the study and the level of ketuntasan of learning at each stage of action learning is done. The value of the results of the student learning experience increased on every cycle of actions taken, namely of 69.22 on the stage of pre cycle, increased to 69.88 at the end of Act I, the Cycle and increased to 74.38 on the end of a Cycle of action II, later increased to 83.25 at the end of Act III Cycle. Finish level learning students experience increased, namely from of 43.75% on pre stage cycle, increased to 46.88% at the end of Act I, the Cycle and increased to 68.75% at the end of the action Cycle II, then rose to 90.63% at the end of the action Cycle III; and 2) application of the method of inkuiri-based visualization of Sangiran Museum can foster an attitude of historical consciousness in grade VII JUNIOR HIGH Country 2 Surakarta semester lesson I in 2013/2014. This is shown by the increased average score attitude awareness of history on the students in any stage of the action learning is done.